1997
DOI: 10.1901/jaba.1997.30-601
|View full text |Cite
|
Sign up to set email alerts
|

Using Neutralizing Routines to Reduce Problem Behaviors

Abstract: Establishing operations can alter problem behaviors by changing the momentary value of reinforcers associated with those problem behaviors. If establishing operations (EOs) precede the presentation of discriminative stimuli (SDs) for problem behaviors, it may be possible to introduce neutralizing routines that both reduce the value of reinforcers associated with problem behaviors and decrease the occurrence of problem behaviors. The present study examined this logic with 3 adolescents with severe intellectual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 17 publications
1
83
1
Order By: Relevance
“…Providing high levels of social contact before treatment sessions functioned as an AO and reduced the occurrence of attention-maintained problem behavior. Likewise, Horner, Day, and Day (1997) reported that sleep deprivation functioned as an EO for the tangible-maintained aggression and self-injury of one boy with autism. Allowing the boy to have a nap appeared to function as an AO and reduced the occurrence of problem behavior.…”
Section: Unconditioned Motivating Operationsmentioning
confidence: 99%
“…Providing high levels of social contact before treatment sessions functioned as an AO and reduced the occurrence of attention-maintained problem behavior. Likewise, Horner, Day, and Day (1997) reported that sleep deprivation functioned as an EO for the tangible-maintained aggression and self-injury of one boy with autism. Allowing the boy to have a nap appeared to function as an AO and reduced the occurrence of problem behavior.…”
Section: Unconditioned Motivating Operationsmentioning
confidence: 99%
“…The proactive environmental design aspect of PBS is seen, for example, in strategies that seek to prevent the recurrence of problem behavior by enhancing opportunities for choice making (e.g., Dunlap et al, 1994), modifying the setting events that alter the valence of reinforcers for significant behaviors (e.g., Horner, Day, & Day, 1997), and restructuring curricula (e.g., Dunlap, Kern-Dunlap, Clarke, & Robbins, 1991). Indeed, the focus on environmental design as a proactive strategy follows logically from the systems change aspect of PBS discussed earlier.…”
Section: Emphasis On Preventionmentioning
confidence: 99%
“…If a behavior is maintained by a particular reinforcement contingency and, with the contingency operative and in the presence of relevant S D s, the behavior sometimes occurs at high rates and sometimes at low rates, the operation of an EO might be suspected. A number of studies have now shown reductions in such variability when EOs are detected and manipulated (Horner, Day, & Day, 1997;Kennedy & Meyer, 1996;O'Reilly, 1995O'Reilly, , 1997Smith et al, 1995).…”
Section: Including the Analysis Of Eos In Functional Analysismentioning
confidence: 99%
“…Although these methods have been used primarily to detect reinforcement contingencies, they all, in principle, can be modified to detect EOs and, in many cases, have already been so used. Horner et al (1997) interviewed the staff working with 3 individuals to identify putative EOs for their problem behavior and subsequently used an alternating treatments design to demonstrate their evocation of problem behavior. Although some approaches to the observation of correlations between environmental events and problem behavior (e.g., ABC charts) have limitations resulting from their focus on the immediate antecedents of behavior, they do typically enable the detection of EOs that immediately precede problem behavior (e.g., demands).…”
Section: Including the Analysis Of Eos In Functional Analysismentioning
confidence: 99%